Association of Cognitive and Behavioral Features Between Adults With Tuberous Sclerosis and Frontotemporal Dementia - Liu, Andy J; Staffaroni, Adam M; Rojas-Martinez, Julio C; Olney, Nicholas T; Alquezar-Burillo, Carolina; Ljubenkov, Peter A; La Joie, Renaud; Fong, Jamie C; Taylor, Joanne; Karydas, Anna; Ramos, Eliana Marisa; Coppola, Giovanni; et al. (Archives of neurology (Chicago), 2020)
Individuals with tuberous sclerosis complex can develop a progressive neuropsychiatric syndrome known as tuberous sclerosis-associated neuropsychiatric disorders. Tuberous sclerosis-associated neuropsychiatric disorders symptoms overlap with clinical criteria for frontotemporal dementia, yet the association between the 2 has not been explored. To investigate the potential association between tuberous sclerosis-associated neuropsychiatric disorders and frontotemporal dementia. Case-control study that enrolled patients with tuberous sclerosis complex with normal IQs in an observational clinical study at the University of California, San Francisco, from 2017 to 2019 where they underwent a comprehensive clinical evaluation including neuropsychologic testing, cerebral spinal fluid biomarker profiling, and structural neuroimaging. The study included adults who fulfilled the clinical criteria for tuberous sclerosis complex and had normal IQs, had frontotemporal dementia, or were healthy control individuals. Tuberous sclerosis-associated neuropsychiatric disorders checklist severity score, neuropsychologic test scores, cerebral spinal fluid concentrations of phosphorylated tau181, total tau, amyloid-β 42, and neurofilament light chain. Amyloid and tau positron emission tomography scans were obtained in a subset of patients. Eighteen patients with tuberous sclerosis complex (mean [SD] age, 48 years [9.54]; 13 women [72%]), 16 with frontotemporal dementia (60 [6.93] years; 7 women [44%]) and 18 healthy control individuals (63 [3.85] years; 9 women [50%]) were included. The tuberous sclerosis-associated neuropsychiatric disorders checklist and neuropsychological test results were not significantly different when the tuberous sclerosis complex and frontotemporal dementia cohorts were compared. The tuberous sclerosis complex cohort exhibited elevated cerebral spinal fluid phosphorylated tau181 and neurofilament light chain with a mean of 32 pg/mL and 2300 pg/mL, respectively, when compared to healthy control individuals. All 3 patients with tuberous sclerosis complex who underwent fluorine 1B-labeled flortaucipir tau positron emission tomographic neuroimaging showed punctate foci of elevated [18F]flortaucipir binding in the frontal and temporal regions. Adults with tuberous sclerosis complex showed phenotypic overlap with frontotemporal dementia. The results support a possible clinical continuum between tuberous sclerosis-associated neuropsychiatric disorders and frontotemporal dementia and highlights a potential pathophysiological link between neurodevelopmental and neurodegenerative processes. Quantitative neuropsychological testing and the tuberous sclerosis-associated neuropsychiatric disorders checklist, potentially supplemented by cerebral spinal fluid and imaging biomarkers, could be used to screen and prognosticate for risk of a neurodegenerative process in adult patients with tuberous sclerosis complex.